Credit Guarantee Schemes for SME lending in Western Europe - Moustafa Chatzouz; Áron Gereben; Frank Lang; Wouter Torfs (European Investment Fund (EIF), 2017)
This report discusses the activity of credit guarantee schemes (CGSs) in Western Europe and presents an analysis based on a novel survey, conducted by the European Investment Bank (EIB) Group1, among 18 credit guarantee organisations in 13 countries and 33 banks operating in 17 countries. The report aims at providing a deeper insight into the driving motives and operational mechanisms of CGSs, and the financial intermediaries that use them. The current publication is a successor of an earlier report, published in 2014 by the European Bank Coordination "Vienna Initiative" Working Group on CGSs (EBCI, 2014), which provides a comprehensive overview on the use of CGSs for Small- and Medium-sized Enterprise (SME) lending in Central, Eastern and South-Eastern Europe (CESEE).
Keywords: 330